193k views
2 votes
Multiply and simplify. 3(x2 + 5)(x2 - 5)

User Nicko Po
by
5.4k points

2 Answers

4 votes

Answer:

3 x^4 + -75

Explanation:

Expand the following:

3 (x^2 + 5) (x^2 - 5)

(x^2 + 5) (x^2 - 5) = (x^2) (x^2) + (x^2) (-5) + (5) (x^2) + (5) (-5) = x^4 - 5 x^2 + 5 x^2 - 25 = x^4 - 25:

3 x^4 - 25

3 (x^4 - 25) = 3 x^4 + 3 (-25):

3 x^4 - 25×3

3 (-25) = -75:

Answer: 3 x^4 + -75

User Karol F
by
5.3k points
3 votes

Answer:

3 x^4 + -75

Explanation:

User JerryZhou
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.